The Essential Tremors: Evolving Concepts of a Family of Diseases - Louis, Elan D. (Frontiers in Neurology, 2021)
The past ten years has seen a remarkable advance in our understanding of the disease traditionally referred to as “essential tremor” (ET). First, the clinical phenotype of ET has been expanded from that of a bland, unidimensional, monosymptomatic entity to one with a host of heterogeneous features. These features include a broader and more nuanced collection of tremors, non-tremor motor features (e.g., gait abnormalities) and a range of non-motor features, including cognitive, psychiatric, sleep and other abnormalities. The natural history of these features, as well as their relationships with one another and with disease duration and severity are better appreciated than they were previously. Studies of disease etiology have identified a number of candidate genes as well as explored several environmental determinants of disease. In addition, the decade has seen the beginnings and expansion of rigorous postmortem studies that have identified and described the postmortem changes in the brains of patients with ET. This emerging science has given rise to a new notion that the disease, in many cases, is one of cerebellar system degeneration. Across all of these studies (clinical, etiological, and pathophysiological) is the observation that there is heterogeneity across patients and that “essential tremor” is likely not a single disease, but rather, a family of diseases. The time has come to use the more appropriate terminology, “the essential tremors”, to fully describe and encapsulate what is now apparent. In this paper, the author will review the clinical, etiological, and pathophysiological findings, referred to above, and make the argument that the terminology should evolve to reflect advances in science, and that “the essential tremors” is a more scientifically appropriate term.